Thermomechanical and damage characterisation of short glass fibre reinforced polyamide 6 and impact-modified polyamide 6 composites - Song, P; Trivedi, A; Chapman, D; Graham, A; Hawkins, N; Lukić, B; Rack, A; Siviour, C (University of Oxford, 2024)
Data to support this publication in the journal Composites Part B